Causes of the diurnal variation observed in gamma-ray spectrum using NaI (Tl) detector. (1st October 2020) - Datar, Gauri; Vichare, Geeta; Selvaraj, C.; Bhaskar, Ankush; Raghav, Anil
Abstract: Present paper studies the γ -ray spectrum observed using NaI (Tl) scintillation detector over a year. The paper reports the presence of a distinct diurnal pattern in the total number of γ -ray counts detected by the NaI detector. The counts start decreasing after sunrise and show gradual recovery after sunset. The amplitude of this variation is quite significant ( > 10%) at the observation site Tirunelveli, South India. However, further investigation based on different energy ranges reveals that the mentioned diurnal pattern is actually present only in the energies related to the terrestrial background radioactivity. The study demonstrates that the pattern is associated with the radioactivity of isotopes of radon ( 222 Rn and 220 Rn) and their daughter radionuclides. The amplitude of the diurnal variation is found to have seasonal dependence, with the lowest amplitude during June–October ( ∼ 2%), and highest in April–May months ( ∼ 14%). The dependence of the amplitude of the diurnal variation on various atmospheric parameters, namely temperature, relative humidity, and the vertical wind is examined. The observed diurnal pattern is attributed to the generation of the inversion layer. The distribution of concentration of radon and thoron progenies in an air column changes with the vertical mixing and atmospheric boundary layer (ABL), resulting in the diurnal variation of γ -rays. The observed lower amplitudes in the months of June–October may be due to the presence of downward winds restricting the radon movement to a thin layer, giving smaller amplitudes of the diurnal variation in total γ -ray flux resulting in seasonal variation. Highlights: A diurnal pattern is evident in γ -ray counts detected by NaI scintillation detector. The pattern is found to be associated with the radon and thoron progenies in the air. It is controlled by the atmospheric vertical mixing, inversion, and boundary layer. The amplitude of the diurnal variation has strong seasonal dependence.